"As if!" in Thunder. (22nd February 2022) - Fleissner, Jennifer L
Abstract: The crises of 2020, this essay argues, demonstrated anew both the dangers and the indispensability of state power. Yet Americanist critics often display the same antistatism that characterized the nation's canonical literature as well as those who championed it in the mid-twentieth century. For an alternative, this essay turns to the work of Lora Romero, a critic who linked those canonical works to political criticism inspired by Michel Foucault. The libertarianism of both, she argued, made it impossible for critics to conceive that "resistance" and "entanglement in power relations" might go hand in hand. The Foucauldian critique of biopolitics is here shown to be inseparable from a skepticism toward an often feminized welfare state linking France's Second Left to figures in the US like Christopher Lasch. Eve Kosofsky Sedgwick's argument against Foucauldian "critique" is then shown to offer a more recent, albeit equally overlooked, resource for taking the necessity of institutionality seriously. Without such correctives, American Studies Association calls for papers can inadvertently echo the "romantic" rhetoric of books like Huckleberry Finn, in which an absolutized freedom and care for all will simply coexist harmoniously, rather than representing two conflicting strands of the modern polis requiring constant negotiation. In our instinctive antistatism and the conception of freedom it entails, we may share more in common than we recognize with the "American ideology" that . . . has formed the object of our ongoing critique.